Learning Through Scenario Planning - Jose Daniel Balarezo (Copenhagen Business School (CBS), 2015)
This project investigates the uses and effects of scenario planning in companies operating in highly uncertain and dynamic environments. Whereas previous research on scenario planning has fallen short of providing sufficient evidence of its mechanisms and effects on individual or organizational level variables, this research corrects this void by investigating the dynamics of organizational learning through the lenses of a corporate scenario planning process. This enhances our scientific understanding of the role that scenario planning might play in the context of organizational learning and strategic renewal. Empirical evidence of the various difficulties that learning flows has to overcome as it journeys through organizational and hierarchical levels are presented. Despite various cognitive and social psychological barriers identified along the way, the results show the novel and counterintuitive ways in which an organization uses scenario planning in balancing the tension between exploration and exploitation. Moreover, this research proposes two novel mechanisms designed to enhance learning flows. At the core of this dissertation are four papers which in combination solidify our theoretical understanding of scenario planning while simultaneously presenting a more nuanced account of the individual behaviors and social dynamics underpinning organizational learning.
hdl:10398/9189
Keywords: 650